First hybrid pigeonpea released - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Plant breeders at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) in India have bred the first hybrid pigeonpea. It is now being released to farmers. This is the first time any pulse crop has been hybridized. The...